Study of pK Values and Effective Dielectric Constants of Ionizable Residues in Pentapeptides and in Staphylococcal Nuclease (SNase) Using a Mean-Field Approach - Bossa, Guilherme Volpe [UNESP]; Fahr, Alfred; Souza, Tereza Pereira de [UNESP] (Amer Chemical Soc, 2014)
The determination of pK values of amino acid residues as a function of temperature and ionic concentration is crucial to understanding the dynamics of various biological processes such as adsorption of peptides and their interactions with active sites of enzymes. In this study we developed a mean-field model to calculate the position-dependent dielectric constants of ionizable groups and the mean electrostatic potential on the surface. Such potential, which takes into account the contributions exerted by neighboring groups and ions in solution, is responsible for the fine-tuning of the pK value of each residue. The proposed model was applied to the amino acids Asp, Glu, Lys, His, Tyr, and Cys, and since the results were consistent with experimentally obtained values, the model was extended and applied to computation of pK values of Gly and Ala pentapeptides and of ionizable residues of the enzyme staphylococcal nuclease (SNase). In this latter case, we used an approach similar to a first-neighbors approximation, and the results turned out to be in good agreement with previously reported data when considering only the interactions of charged groups located at distances of maximally 20 angstrom. These considerations and the little computational cost involved turn the suggested approach into a promising tool for the modeling of force fields in computational simulations.